Komunikasi Dalam Kehidupan Beragama Melalui BISINDO - Muniksu, I Made Sukma (Institut Hindu Dharma Denpasar, 2021)
Living in a social and religious life, you will find very rapid differences in communication between Deaf and Hearing Friends. So that each individual must respect and respect each other. In this way, religious harmony will be realized. Listeners can learn BISINDO so they can communicate with Deaf Friends. Listening friends can learn starting from the easiest, namely recognizing letters and numbers. Because through letters and numbers can provide symbols that are very useful in communication. Communication is a basic human activity. There is not an individual who will not be involved in communication. In this relationship in communication, it is in the form of tolerance and information between religious communities which are the core elements of limited religious harmony within the internal environment of a religion. Meanwhile, horizontal relationships, or patterns of human relations with each other or humans with surrounding communities of different cultures, races, religions, be it in the form of social cooperation or individual patterns with individuals to build a stronger sense of brotherhood. A society with a social and religious life definitely needs communication. Even though the communication occurred between Listening Friends and Deaf Friends. All activities that occur in religious life cannot be separated from the communication from the communicator to the communicant. A deaf friend who uses BISINDO as a communicant has the right to know what information he gets from other people. In a diverse life, Teman Deaf also has the right to receive religious teachings that he believes in.